Role of automation in site accidents avidness in the construction industry: A Review - Musarat, M.A. (Institute of Electrical and Electronics Engineers Inc., 2021)
The construction industry is occupational health and safety (OHS) concern worldwide due to its highest rate of workplace injuries. Notwithstanding the advancements in construction technologies, records of high fatality and injury rates still plague the construction industry. Thus, this review is undertaken to evaluate the studies on automation in construction to avoid occupational hazards and accidents. Accordingly, the PRISMA statement was applied, and the Scopus database was searched for data extraction. Based upon the search criteria, initially, 65 articles were drawn out. After performing the screening, duplication check, and quality assessment a total of 19 articles were selected for further evaluation. The keywords combination 'Automation' AND 'Accident' AND 'Safety' AND 'Construction' with year range from 2011 to 2021 were used as Scopus database search criteria. The extracted articles were focusing on the automated solutions for the leading causes of site accidents i.e. trip fall, electrocution and struck by equipment. The studies include various Building information Modeling (BIM) frameworks to analyze the models in the design planning phase for identifying built-in hazards. Also, automation technologies such as real-time location services (RTLS), radio frequency identification (RFID), wireless sensor network (WSN) are employed for real-time identification and prevention of safety hazards. The adoption of these automation approaches in construction safety management may reduce the high fatality and accident rate in the engineering construction industry. Â© 2021 IEEE.